Fraksionasi Fosfor pada Profil Tanah Hutan, Wanatani, dan Tegalan di Jawa Barat - Parjono Parjono; Syaiful Anwar; Kukuh Murtilaksono; Lilik Tri Indriyati (Jurnal Ilmu Pertanian Indonesia, 2019)
This study aims to evaluate the distribution of phosphorus (P) fractions within the soil horizons or profile of forest, agroforestry, and dryland in West Java and their correlations with soil chemical properties. Evaluation was based on the analytical results of soil samples taken from four soil horizons (Ao or Ap, A1 or A2, B1, and, B2) in each land use types. Fractionation of soil P was carried out using a sequential extraction method to get readily available-P (NaHCO3-P-inorganic (i)-P-organic (o)), rather available-P (NaOH-Pi-Po), slowly available-P (HCl-Pi), not available-P (residual-P), and total-P (HCl25%-P) fractions. The results showed that the average concentration of soil residual-P fraction in all land use types reached >99% of the total-P. The highest average concentration of residual-P fraction was measured in dryland, followed by forest and agroforestry. This indicated that soil P adsorption capacity was very high and resulted in a very low concentrations of the soil available-P fractions. The high concentrations of soil residual-P and total-P fractions were most probably related to P fertilizer application, particularly in dryland soil. Distributions of P fractions within the soil horizons at all land use types were significantly correlated with the concentration of soil organic matter content. It is therefore the concentration of soil NaOH-Po fraction was decreasing with the soil depths. The highest concentration was found at Ao or Ap horizon, although it was not the case for NaOH-Po fractions that was relatively constant.